Improved Detection of HIV Gag p24 Protein Using a Combined Immunoprecipitation and Digital ELISA Method - Wu, Guoxin; Cheney, Carol; Huang, Qian; Hazuda, Daria J.; Howell, Bonnie J.; Zuck, Paul (Frontiers in Microbiology, 2021)
Greater than 90% of HIV-1 proviruses are thought to be defective and incapable of viral replication. While replication competent proviruses are of primary concern with respect to disease progression or transmission, studies have shown that even defective proviruses are not silent and can produce viral proteins which may contribute to inflammation and immune responses. Viral protein expression also has implications for immune-based HIV-1 clearance strategies which rely on antigen recognition. Thus, sensitive assays aimed at quantifying both replication-competent proviruses and defective yet translationally-competent proviruses are needed to understand the contribution of viral protein to HIV-1 pathogenesis and determine the effectiveness of HIV-1 cure interventions. Previously, we reported a modified HIV-1 gag p24 digital ELISA with single molecule array (Simoa) detection of cell associated viral protein. Here we report a novel p24 protein enrichment method coupled with the digital immunoassay to further extend the sensitivity and specificity of viral protein detection. Immunocapture of HIV gag p24 followed by elution in a Simoa-compatible format resulted in higher protein recovery and lower background from various biological matrices and sample volumes. Quantification of a little as 1 fg of p24 protein from cell lysates from cells isolated from peripheral blood or tissues from ART-suppressed HIV participants, as well as SHIV-infected NHPs, with high recovery and reproducibility are demonstrated here. The application of these enhanced methods to patient-derived samples has potential to further the study of the persistent HIV state, examine in vitro response to therapies, as well as ex vivo study of translationally-competent cells from a variety of donors.